How does hedge designation impact the market’s perception of credit risk? - Anbil, Sriya; Saretto, Alessio; Tookes, Heather (Journal of Financial Stability, 2019)
Non-financial corporations typically cite risk management as the primary reason for their derivatives use. If hedging programs are effective, then firms using derivatives should have lower credit risk than those that do not. Consistent with this idea, we find that CDS spreads are lower for firms with derivatives positions that are designated as accounting hedges (typically low basis risk) compared to firms without the accounting hedge designation as well as firms that do not use derivatives. Surprisingly, we find that firms with derivatives positions without a hedge accounting designation have higher CDS spreads than firms that do not hedge with derivatives at all. We do not find evidence that these non-designated positions are associated with future credit realizations, as captured by changes in either credit ratings or CDS spreads. We examine alternative explanations and find evidence that is consistent with a market penalty for high basis risk positions when overall market conditions are poor.